2003
DOI: 10.1007/s00221-003-1466-9
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of human neck muscle activity following repeated imposed trunk-forward linear acceleration

Abstract: It has been suggested that, after a passive linear acceleration of a seated subject which resembles a small, rear-end car impact, sensory information from proprioceptive, vestibular, and visual systems elicit stabilizing neck muscular responses. These neck muscular responses are presumably reflex based and are modified with the magnitude of the perturbation. A key issue that remains is to determine whether the neck and head postural responses can be modulated by a previous experience of the acceleration and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
52
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 19 publications
7
52
1
1
Order By: Relevance
“…The order of repetitions continued to have an effect during different head postures. These results conform to the results of Blouin et al, and Siegmund et al, who found decreased EMG amplitudes in the neck muscles (sternocleidomastoid, cervical paraspinal, scalenes and trapezius) following repeated forward perturbations [19,29]. The kinematics showed that a significantly decreased peak angle displacement in the neck occurred after the first perturbation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The order of repetitions continued to have an effect during different head postures. These results conform to the results of Blouin et al, and Siegmund et al, who found decreased EMG amplitudes in the neck muscles (sternocleidomastoid, cervical paraspinal, scalenes and trapezius) following repeated forward perturbations [19,29]. The kinematics showed that a significantly decreased peak angle displacement in the neck occurred after the first perturbation.…”
Section: Discussionsupporting
confidence: 91%
“…The kinematics showed that a significantly decreased peak angle displacement in the neck occurred after the first perturbation. Previous studies of forward perturbations have reported both increased head angles and no change in head angles [18,19]. An increased segment angle should be possible as the EMG amplitudes was reduced.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Axial and appendicular muscles respond to acoustic startle (16), but the strongest and most consistent response occurs in the neck muscles, particularly the sternocleidomastoid (SCM) muscle (8). Since consistent neck muscle responses are also evoked by forward accelerations in seated subjects (3,4,6,32,34), the neck muscles are well suited for study of the potential interaction between the acoustic startle response and the postural responses elicited by whole body accelerations.Reflex activation of the neck muscles can be evoked via one or more of the visual, auditory, vestibular, proprioceptive, and cutaneous sensory systems. In some real-world conditions, such as rear-end automobile collisions, all these sensory systems are stimulated, and some form of cross-modal summation likely occurs (45).…”
mentioning
confidence: 99%
“…posture; neck muscle reflexes; habituation POSTURAL RESPONSES RAPIDLY adapt with repeated exposures to the same perturbation in standing (2,19,24), seated (3,34), and supine (2) individuals. This process of adaptation, called habituation (18), typically consists of attenuated muscle activity and related kinematic changes.…”
mentioning
confidence: 99%